PENGARUH PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK, SANKSI PERPAJAKAN DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR(STUDI EMPIRIS DI KABUPATEN KUDUS) - Naufal Tajuddin Mahsun; Sri Mulyani Mulyani; Diah Ayu Susanti (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2026)
This study aims to tezt and analyze the effect of taxpayer knowledge, taxpayer awareness, tax sanctions, and the quality of tax services on motor vehicle taxpayer compliance at the Kudus Regency SAMSAT Office. The population in this study was all taxpayers registered at the Kudus SAMSAT Office. The sampling method used in this study was a purposive sampling method with 410 respondents. The data used were primary data obtained through questionnaires. Data analysis used multiple linear regression analysis. The results of the study indicate that taxpayer knowledge, taxpayer awareness, tax sanctions, and the quality of tax services have a positive effect on motor vehicle taxpayer compliance.